COVID-19 vaccine hesitancy and intentions among parents of children with mental and behavioral disorders - Mohamed Adil Shah Khoodoruth; Sami Ouanes; Kristian Somintac; Shaima Gulistan; Asieh Dehwari; Widaad Nuzhah Chut-Kai Khoodoruth; Mohammed Nasser Alamri; Majid Alabdulla; Yasser Saeed Khan (Taylor & Francis Group, 2024)
Parent vaccine hesitancy (PVH) remains a significant public health concern, particularly emphasized during the COVID-19 pandemic. This study investigates PVH among parents of children with various psychiatric and neurodevelopmental conditions, such as attention deficit hyperactivity disorder (ADHD), anxiety disorders, and behavioral disturbances, extending previous research focused on autism spectrum disorder (ASD). We examined PVH in children aged 5-11 years with psychiatric and behavioral disorders excluding ASD. A cross-sectional questionnaire-based analysis was conducted in Qatar, involving 244 parents of neurodiverse children and 245 parents of neurotypical children as controls. The Parent Attitudes about Childhood Vaccines (PACV) survey assessed PVH. Results indicated a significantly higher prevalence of vaccine hesitancy among parents of children with psychiatric disorders (54.1%, 95% CI [47.8%, 60.4%], n = 132) compared to controls (11.7%, 95% CI [7.5%, 16.0%], n = 26), p < .001. The PACV total score was significantly higher in parents of children with a mental disorder. Higher education among parents and lower PACV scores significantly influenced the intent to vaccinate against COVID-19. Tailored interventions by child and adolescent mental healthcare professionals, such as harnessing artificial intelligence to fight disinformation, are crucial to addressing vaccine hesitancy, enhancing acceptance, and improving outcomes for children with psychiatric disorders.